Enzyme self-label-bound ATTO700 in single-molecule and super-resolution microscopy - Trumpp, M; Oliveras, A; Gonschior, H; Ast, J; Hodson, DJ; Knaus, P; Lehmann, M; Birol, M; Broichhagen, J (Royal Society of Chemistry, 2022)
Herein, we evaluate near-infrared ATTO700 as an acceptor in SNAP- and Halo-tag protein labelling for Förster Resonance Energy Transfer (FRET) by ensemble and single molecule measurements. Microscopy of cell surface proteins in live cells is perfomed including super-resolution stimulated emission by depletion (STED) nanoscopy.